“El programa radial micrófono ciudadano difundido por la emisora eterna primavera como una estrategia de rendición de cuentas del GADM de Pallatanga y su incidencia en la población urbana del cantón en el período junio a diciembre de 2015” - López Zavala, Edwin Alejandro (2016)
The present research work pretends to identify the plan, execution, incidence and importance of a radio show called “Micrófono Ciudadano” as a strategy to present results in the administration of the “Gobierno Autónomo Descentralizado de Pallatanga” which is a process that starts with the referential framework, its outline and the formulation of the problem. Then, the theoretical framework that references the contents related to the independent variable that corresponds to: communication, elements, media, theories, radio, radio program; and the dependent variable that corresponds to: presenting results of administrative actions, The methodological framework establishes the type, level, methods and the design of the study by applying a questionnaire and interviews to the authorities of the GADM and then the analysis and interpretation of results through statistic graphics. As a result, it can be determined the incidence and importance of the radio show called “Micrófono Ciudadano” directed to the population which constitutes an important issue to set new strategies, and update information where the citizens take an active part to establish precise actions. Finally, the study presents a methodological guide to produce radio programs in order to present results of administrative actions.